ON AN ORNITHOMIMID DINOSAUR (SAURISCHIA, ORNITHOMIMOSAURIA) FROM THE CENOMANIAN OF FERGANA - Averianov A.O. (My University, 2006)
A fragmentary coracoid of Ornithomimidae indet. from the Lower Cenomanian of the Abshir River (Kyrgyzstan) is described. This is the first record of this group in a Cenomanian locality of Fergana. The coracoid from the Abshir locality is similar in the lateral deflection of the glenoid to an endemic group of Asiatic Ornithomimidae that includes Anserimimus, Gallimimus, and taxa from the Cenomanian and Turonian of western Uzbekistan. It is most similar to the unnamed ornithomimid from the Cenomanian of Karakalpakia in having a distinct vertical crest that borders anteriorly a depression for the coracobrachialis brevis muscle. Dinosaurs recorded in the Cenomanian of Fergana are reviewed. © Pleiades Publishing, Inc. 2006.
Keywords: ASIA; CENOMANIAN; DINOSAURIA; FERGANA DEPRESSION; KYRGYZSTAN; ORNITHOMIMOSAURIA; Mesozoic::Cretaceous::Upper::Cenomanian; Мезозой::Меловая::Верхний::Сеноманский